«Поетика вогню» Ґ. Башляра як метод аналізу літературних текстів - Радавська, Оксана; Radavska, Oksana (Східноєвропейський національний університет імені Лесі Українки, 2015)
Статтю присвячено аналізу «Поетики Вогню» Ґ. Башляра, що розглядається як метод аналізу літературних текстів на прикладах Фенікса -«природного» образу «Поетики Вогню», Прометея та Емпедокла. На основі творів із французької, російської та української поезії XX ст. показано, що в поезії модернізму трапляються численні приклади «Поетики Вогню». Виявлено, що «Поетику вогню» Ґ. Башляра в зображенні процесу творчості періоду модернізму можна використовувати як метод аналізу літературних текстів, оскільки у всіх описах є спільні акценти. The article is devoted to the analysis of «Poetics of Fire» of Gaston Bashlar that is examined, as a method of analysis of literary texts, on the examples: Phoenix - «natural» image of «Poetics of Fire», Promethei and Empedokl. On the basis of examples from the French, Russian and Ukrainian poetry of 20 century is shown, that in the poetry of modernism there are a lot of examples of «Poetics of Fire», that can be connected with the intensification of the expressionism of the representation means. It was discovered that the language itself becomes the means of the expression of the inner fire, that is the expressive language and poetry creates expressive communication, a dialogue between the reader and the poet. It was discovered that «Poetics of Fire» of Gaston Bashlar, in the representation of the process of the creation of the period of modernism, it is possible to use, as a method of analysis of literary texts, as there are general in all description.
«Poetics of fire» of Gaston Bashlar as a Method of Analysis of Literary Texts.
Keywords: «Поетика Вогню»; «Поетика Фенікса»; «The Poetics of Fire»; «The Poetics of Phoenix»